그림책 표지 디자인의 시각적 구성 요소가 중국 소비자 구매 의도에 미치는 영향 - 한국 그림책의 중국어 번역본을 중심으로 - 서진희; Xu Chenxi; 장미경; Mee-kyung Jang (한국디자인포럼, 2024)
연구배경 한국 출판 산업은 다변화된 독자 요구에 맞춰 해외수출 분야를 강화하고 있으며, 특히 아시아에서 중국 시장은 번역된 한국 그림책의 수요가 꾸준히 증가하고 있다. 이를 기본으로 본 연구자는 중국으로 수출된 한국 그림책의 중국어 번역판 표지 디자인으로 연구 주제를 한정 짓고 소비자의 구매 의도 간의 관계를 실증 분석 및 탐구하여 출판사와 디자이너에게 전략적 시각과 창작 지침을 제공하는 것을 목적으로 한다. 연구방법 본 연구는 문헌 연구, 사례 연구, 실증 연구의 세 가지 방법을 통해 진행되었다. 문헌 연구로 이론적 근거를 마련하고, 사례 연구로 한국 그림책 중국어 번역 본 표지 디자인을 분석하였다. 실증 연구에서는 중국 소비자 266명을 대상으로 설문조사를 실시하여 시각적 요소와 구매 의도 간의 관계를 분석하였다. 연구결과 한국 그림책의 중국어 번역본 표지는 현지 문화와 소비자 선호도를 반영하여 타이포그래피와 레이아웃에 변화를 주었다. 상위 10위 안에 드는 한국 그림책의 중국어 번역본은 주로 주제와 관련된 컬러, 고딕체 타이포그래피, 만화 스타일의 일러스트, 대칭 및 중심 맞춤 레이아웃을 사용하며, 책의 수상 정보를 추가하는 경우가 많았다. 실증 연구 결과, 표지 디자인의 시각적 요소는 중국 소비자의 구매 의도에 큰 영향을 미쳤으며, 특히 일러스트레이션의 영향이 가장 컸다. 수상 정보는 컬러, 타이포그래피, 일러스트레이션과 구매 의도의 관계에서 긍정적인 조절 역할을 하였다. 결론 글로벌 시장을 목표로 하는 출판 사업의 표지 디자인은 현지 문화와 소비자 선호를 반영한 맞춤형 디자인 전략을 채택해야 한다. 그러므로 신뢰도와 구매 의도를 높이기 위해 수상 정보와 일러스트레이션을 활용해야 하며 지속적인 시장 조사와 전략 업데이트가 필요하다. Background The Korean publishing industry is strengthening its exports to meet the diverse demands of readers, especially with the increasing demand for picture books in the Chinese market. This study aims to explore the relationship between the cover design of Korean picture books translated into Chinese and the purchase intentions of consumers. The goal is to provide strategic insights for publishers and guidelines for designers. Methods This study employed three methods: literature review, case study, and empirical research. The literature review established the theoretical basis for picture book cover design and consumer purchase intentions. The case study analyzed the cover designs of Korean picture books translated into Chinese. Finally, empirical research involved a survey of 266 Chinese consumers to analyze the relationship between visual elements and purchase intentions. Result The cover designs of Korean picture books translated into Chinese were adapted to reflect local culture and consumer preferences, particularly in typography and layout. The top 10 Korean picture books in the Chinese market predominantly used colors related to the theme, Gothic typography, cartoon-style illustrations, and symmetrical and centered layouts, often including award information. The empirical research showed that the visual elements of cover design (color, typography, illustration, layout) positively influenced Chinese consumers' purchase intentions, with illustrations having the greatest impact. Award information on the cover positively moderated the relationship between color, typography, illustration, and purchase intention, significantly enhancing consumer trust and quality expectations. Conclusion To target the global market, Korean publishing businesses should adopt tailored design strategies that reflect local culture and consumer preferences. Utilizing award information and illustrations to increase trust and purchase intentions. Continuous market research and strategy updates are also necessary.